Analysis of Consumer Purchasing Behavior in The Frozen Food Industry: A Case Study of Dapur Tembem - Khoirunnisa, Aisyah; Sumarwan, Ujang; Yuliati, Lilik Noor (Business Review and Case Studies, 2025)
Background: The frozen food industry in Indonesia is experiencing rapid growth owing to changing lifestyles, increasing digital access, and consumer demand for convenience. However, Dapur Tembem, a local SME, has faced a sharp decline in sales, despite these opportunities. Purpose: This study examined the influence of brand awareness, perceived price, electronic word of mouth (e-WoM), and resellers on purchase behavior, with brand trust serving as a mediating variable. The goal was to generate practical marketing recommendations to support sales recovery. Design/methodology/approach: A quantitative approach was used with structural equation modeling partial least squares (SEM-PLS) on survey data collected from 120 consumers selected through purposive sampling. Respondents met the following specific criteria: they had purchased and consumed Dapur Tembem frozen food products at least twice, with their most recent purchase occurring no later than October 2024. Findings/Result: Brand trust is the most influential factor in driving purchase behavior and mediates the effects of perceived price, e-WoM, and resellers. e-WoM directly affects purchase behavior, whereas brand awareness does not have a significant impact. Conclusion: Consumers perceive fair pricing, reseller credibility, and online recommendations as the key drivers of trust and purchase intent. These results suggest that Dapur Tembem should focus on strengthening brand trust through strategic pricing, reseller optimization, and digital engagement. Originality/value (State of the art): This study offers new insights into the role of brand trust and resellers in influencing consumer behavior, especially in the context of SMEs in Indonesia’s frozen food sector, with Instagram identified as the most effective engagement platform. Keywords: brand trust, electronic word of mouth, perceived price, purchase behavior, reseller